Regularity of Poisson quadratic stochastic operator generated by 2-partition of a singleton - Mohd Fadzullah, Nur Alis Aqeelah; Hamzah, Nur Zatul Akmar; Ganikhodjaev, Nasir (UMT Press, 2024)
The theory of quadratic stochastic operator (QSO) was developed by Bernstein in 1924 when he presented about population genetics. The research on QSO is still ongoing as researchers have not yet studied various classes, conditions, and measures. In this paper, we introduce a new class of Poisson QSO generated by the 2-partition of a singleton defined on the set of all integers state space. We illustrate the trajectory behaviour of the constructed QSO by cases. Lastly, we show that it is a regular transformation for some parameters’ values.